ECO-FRIENDLY SYNTHESIS OF SILVER NANOPARTICLES BY USING GREEN METHOD: IMPROVED INTERACTION AND APPLICATION IN VITRO AND IN VIVO. - & Hayder, Atwan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The present study was aimed to biosynthesis of silver nanoparticles by using rhaminolipid produced from local isolate Pseudomonas aeruginosa as reducing and stabilizing agent. Silver nanoparticles (AgNPs) synthesized by green method have shown several applications such as biomedical, anticancer, bio sensing, catalysis etc. Characterization study of purified bioemulsifier using thin layer chromatography (TLC) was demonstrated that the biosurfactant contains mono, and di- rhamnolipid with Rf values of 0.86 and 0.36 respectively. Optimization results of biosynthesis silver nanoparticles were revealed that an increasing in intensity of Surface Plasmon Resonance (SPR) bands of nanoparticles with shifting at wavelength (400 nm). Also optimum synthesis of AgNPs was at pH 5, Temperature 40℃, reaction time 5 minutes with concentration of rhaminolipid as reducing agents (2×10-3w/v) and Silver ion concentration (6×10-3 mol/L).  The result of X-ray diffraction was indicated that the size of silver nanoparticles observed was 38 nm and show relatively stable peak at -23.2 mV. Finally, the minimum inhibitory concentration of Ag NPs against human pathogenic bacteria obtained at concentration (1mg/ml) for both gram negative and gram-positive bacteria. The results of anti-inflammatory effects of Ag NPs obviously, cleared that the infection of test animals treated with AgNPs were completely healed after 6 days of treatment, while the animals treated with fucidin (as control) not exhibited any healing in the infection.